112 BILATERAL PNEUMOTHORACES SECONDARY TO PULMONARY METASTASES FROM A WILMS' TUMOR: A CASE REPORT. Issue 1 (1st January 2007) - Bolton, M.; Trivedi, Y.; Wheat, S.; Bass, P.
Abstract : Case Report: This is a 29-year-old AA male who initially presented to the LSU Urology Department complaining of difficulties in urinating. Initial cystoscopy revealed a necrotic mass at the base of the bladder as well as a prostatic urethral mass that pathology reported as an abscess with necrotic and hemorrhagic entities but negative for malignancy. Pathology slides were sent to the Armed Forces Institute of Pathology and resulted in a diagnosis of Wilms' tumor. The patient underwent a cystoprostatectomy and then received chemotherapy at LSU for approximately three cycles of VIP (cisplatin, ifosfamide, etoposide) that ended 2 months prior to his first presentation with a pneumothorax. The patient was treated at an outside hospital for recurrent pneumothoraces requiring multiple chest tubes and actually underwent a video-assisted thoracoscopy bilaterally just under 2 months prior to this presentation. The patient presented at this admission after having been discharged just 4 days earlier for a right-sided pneumothorax. The patient was evaluated by the Pulmonary Service as well as the Cardiothoracic Surgery Service, both of which felt that there was no further beneficial intervention that could be performed at this time. Referral to the Hematology/Oncology Service was made, which felt that further chemotherapy would not be beneficial to the patient. He was subsequently discharged to home hospice with oxygen. Pneumothoraces secondary to nephroblastic metastatic lesions are rare. In fact, less than 1% of all spontaneous pneumothoraces are a result of pulmonary metastasis. Most complicating pneumothoraces have been seen with metasatic osteosarcomas, although synovial sarcomas, Ewing's tumors, and hemangioendotheliosarcomas have been reported. Previous reports have noted such a complication in patients undergoing chemotherapy or radiation therapy. Gordon et al reported a case involving metasatic disease in a 14-year-old who presented with pneumothorax 10 years after chemotherapy. All previous case reports have documented such rare complications in children, which is the most common population to have a diagnosis of a Wilms' tumor. It is not surprising, then, that previously documented, albeit rare, complications such as recurrent pneumothoraces can happen in an adult with stage IV nephroblastoma. Multiple hypotheses have tried to account for this phenomenon. A ball-valve mechanism secondary to tumor burden intruding on bronchioles and bronchi, causing cavitary lesions, and evolving into thin-walled cysts. Rowinsky et al proposed a necrotic process of pulmonary lesions that cavitate secondary to poor blood supply, resulting in the rare complication we are presenting in this case report. Another possibility for pneumothoraces in such patients could be radiotherapy causing fibrosis leading to mild or moderate pneumothorax. This method does not apply to our particular patient since he never received radiotherapy.